Description Of Anxiety, Depression, And Stress In Diploma Nursing Students Caring For The Elderly During Clinical Practice - Sianipar, Claudia Vytha Cantica; Simbolon, Idauli (Fakultas Ilmu Keperawatan Universitas Klabat, 2025)
Clinical practice is beneficial in gaining definite experience to achieve professional skills including knowledge, technical and social skills or good communication. However, during the practical placement, often nursing students experience anxiety, depression and stress. This study aims to describe the level of anxiety, depression and stress experienced, identify the factors causing anxiety faced, and identify coping strategies used by D3 Nursing students in overcoming anxiety, depression and stress when caring for the elderly during clinical practice in hospitals. This study uses a mixed method with explanatory sequential design. The study population is D3 Nursing students of Surya Nusantara University who care for the elderly during clinical practice in hospitals, while the sample is total sample of 30 students for quantitative data, and 5 students based on data saturation for qualitative data. Data collection procedures used the DASS 21 (Depression Anxiety Stress Scale 21) instrument for qualitative data, and an online interview using zoom meeting by initiating open-ended questions for qualitative data. Qualitative data is analyzed using SPSS descriptive analysis while qualitative data is analyzed through content analysis. Both quantitative and qualitative found that nursing students were experience anxiety, depression, and stress with various level of anxiety, depression and stress from range of mild to very severe with anxiety occupying the most prominent position compared to the other two conditions. Based on qualitative data, the cause, the symptoms, and copying strategy for anxiety, depression, and stress are also found. The recommendations are directed toward preceptors, nursing students themselves and their junior. Praktik klinis bermanfaat dalam memperoleh pengalaman nyata untuk mencapai keterampilan profesional, termasuk pengetahuan, keterampilan teknis dan sosial, atau komunikasi yang baik. Namun, selama praktik kerja, mahasiswa keperawatan seringkali mengalami kecemasan, depresi, dan stres. Penelitian ini bertujuan untuk mendeskripsikan tingkat kecemasan, depresi, dan stres yang dialami, mengidentifikasi faktor-faktor penyebab kecemasan yang dihadapi, dan mengidentifikasi strategi koping yang digunakan mahasiswa D3 Keperawatan dalam mengatasi kecemasan, depresi, dan stres saat merawat lansia selama praktik klinis di rumah sakit. Penelitian ini menggunakan metode campuran dengan desain ekplanatory sequential. Populasi penelitian adalah mahasiswa D3 Keperawatan Universitas Surya Nusantara yang merawat lansia selama praktik klinis di rumah sakit, sedangkan sampel penelitian adalah total sampel sebanyak 30 mahasiswa untuk data kuantitatif, dan 5 mahasiswa berdasarkan saturasi data untuk data kualitatif. Prosedur pengumpulan data menggunakan instrumen DASS 21 (Depression Anxiety Stress Scale 21) untuk data kualitatif, dan wawancara daring menggunakan zoom meeting dengan mengajukan pertanyaan terbuka untuk data kualitatif. Data kualitatif dianalisis menggunakan analisis deskriptif SPSS, sedangkan data kualitatif dianalisis melalui analisis isi. Baik secara kuantitatif maupun kualitatif, ditemukan bahwa mahasiswa keperawatan mengalami kecemasan, depresi, dan stres dengan berbagai tingkat kecemasan, depresi, dan stres, mulai dari ringan hingga sangat berat, dengan kecemasan menempati posisi paling menonjol dibandingkan dua kondisi lainnya. Berdasarkan data kualitatif, penyebab, gejala, dan strategi meniru kecemasan, depresi, dan stres juga ditemukan. Rekomendasi ditujukan kepada preceptor, mahasiswa keperawatan itu sendiri, dan junior mereka.